2021
DOI: 10.1038/s41559-021-01586-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of tumour growth impact clonal diversification in a computational model and the TRACERx Renal study

Abstract: Genetic intra-tumour heterogeneity fuels clonal evolution, but our understanding of clinically relevant clonal dynamics remain limited. We investigated spatial and temporal features of clonal diversification in clear cell renal cell carcinoma through a combination of modelling and real tumour analysis. We observe that the mode of tumour growth, surface or volume, impacts the extent of subclonal diversification, enabling interpretation of clonal diversity in patient tumours. Specific patterns of proliferation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…Increased local tension induces the expression of cancer stem cell markers and modulates cell shape, adhesion, and signaling [14]. Tumor growth and shape, conditioned by mechanical tension and spatial restrictions among other factors, affect the diversification of genetic subclones in clear cell renal carcinoma, demonstrating crosstalk between cellular and architectural intratumor heterogeneity that impacts on cancer evolution [15]. The use of spatial transcriptomics and single-cell RNA sequencing in human pancreatic ductal adenocarcinoma (PDAC) allowed the correlation of transcriptomic signatures and stromal enrichment with spatially isolated architectures within a tumor [16].…”
Section: Open Accessmentioning
confidence: 99%
“…Increased local tension induces the expression of cancer stem cell markers and modulates cell shape, adhesion, and signaling [14]. Tumor growth and shape, conditioned by mechanical tension and spatial restrictions among other factors, affect the diversification of genetic subclones in clear cell renal carcinoma, demonstrating crosstalk between cellular and architectural intratumor heterogeneity that impacts on cancer evolution [15]. The use of spatial transcriptomics and single-cell RNA sequencing in human pancreatic ductal adenocarcinoma (PDAC) allowed the correlation of transcriptomic signatures and stromal enrichment with spatially isolated architectures within a tumor [16].…”
Section: Open Accessmentioning
confidence: 99%
“…Phylogenetic reconstruction revealed branched evolutionary tumor growth, demonstrating that sub-clones evolved with tumor progression 29 31 . In solid tumors, various immune and stromal cells in TME coevolve with the tumor progression, and the evolution of TME may influence the prognosis and treatment of tumors 11 13 . Consequently, trajectory-based differential expression analysis can assist scholars to better understand the evolution of ITH and TME.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a series of studies showed the deterministic nature of clonal evolution with the progression of tumors, and the evolutionary landscape in ccRCC was dominated by ITH 6 10 . Meanwhile, with the change of tumor genome, the tumor microenvironment (TME) may consequently change, and vice versa 11 . The transformation of content and properties of TME caused by the coevolution of tumor and non-tumor cells may have different effects on the prognosis and treatment of RCC 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The tumor periphery may hence represent a spatial niche that harbors tumor cells with an increased fitness or potentially higher aggressiveness. A recent study used computational modeling to suggest that such a “surface growth” pattern could be associated with an enhanced subclonal diversification ( 37 ). While this computational study did not include the microenvironment as a factor that may influence tumor growth, it nevertheless underscores that tumor evolution and growth patterns are very likely connected.…”
Section: Genomic and Functional Intratumoral Heterogeneity (Ith)mentioning
confidence: 99%